Composite material with high relative crystallinity and preparation method thereof

By using MXene/CNC composite fillers in natural rubber, the mechanical properties and relative crystallinity of the composite material are improved, and the problems of improved performance and insufficient resistance of natural rubber composite materials are solved, achieving a wider application prospect.

CN119192691APending Publication Date: 2024-12-27AVIC BEIJING INST OF AERONAUTICAL MATERIALS

Patent Information

Application Number
CN202411369396.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

There is room for improvement in the mechanical properties and strain-induced crystallization properties of existing natural rubber composite materials, and their oil resistance, organic solvent resistance, thermal oxygen aging resistance and ultraviolet resistance are poor, which limits its application range.

Method used

The MXene/CNC composite filler is used as the reinforcement material for natural rubber. By preparing the combination of MXene/CNC composite filler and natural rubber, the relative crystallinity and mechanical properties of the composite material are improved by using vulcanization processing and mechanical properties.

Benefits of technology

It significantly improves the self-reinforcement and mechanical properties of natural rubber, enhances the relative crystallinity of composite materials, improves its oil resistance, organic solvent resistance and ultraviolet resistance, and improves its applicability in special applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192691A_ABST
    Figure CN119192691A_ABST
Patent Text Reader

Abstract

The invention provides a rubber composition, a composite material and a preparation method thereof, and relates to the field of rubber materials. The invention provides a rubber composition which comprises natural rubber and filler, the filler comprises MXene and cellulose nanocrystals, and the invention further provides a rubber composite material comprising the rubber composition, a vulcanizing agent, an accelerant and an activating agent. According to the invention, the MXene and the cellulose nanocrystals are used as fillers to play a synergistic reinforcing role, so that the mechanical property and the self-reinforcing property of the rubber composite material are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber materials, and in particular to a rubber composition, a composite material with high relative crystallinity and a preparation method thereof. Background Art

[0002] Natural rubber (NR), as a renewable natural resource with superior comprehensive properties, has the characteristics of high elasticity, high strength, high elongation and wear resistance. It is widely used in aerospace, national defense, aircraft tires, medical elastomers and other fields, and occupies a very important position in economic construction. However, NR is a non-polar rubber. Although it does not react much in polar solvents, it is easy to react with hydrocarbon organic solvents, so its oil resistance and organic solvent resistance are poor; in addition, NR molecules contain unsaturated double bonds, so its resistance to thermal oxidation aging, ozone resistance and UV resistance are poor, all of which limit its application in some special occasions. For a long time, the modification of NR has been considered a feasible method for producing new natural rubbers with special properties, and it is an enduring research field for NR.

[0003] In the prior art, the comprehensive properties of natural rubber are mostly improved by filler modification. Chinese patent CN108299687A discloses a natural rubber composite material prepared by a wood cellulose / montmorillonite / carbon black-white carbon black bidirectional filler composite reinforcing agent, wherein the composite reinforcing agent has good compatibility with natural rubber and significantly improves the physical properties of rubber. Chinese patent CN 103224656A discloses a graphene oxide / carbon black rubber nanocomposite material and a preparation method thereof, wherein natural rubber, styrene-butadiene rubber, butadiene rubber and a mixture thereof are used as a matrix, and a graphene / carbon black rubber composite material is prepared by an emulsion method. Chinese patent CN 107457933 discloses a filler / rubber composite material preparation method, wherein the composite material is prepared by three main steps of preparing a masterbatch mixture, preparing a masterbatch, and preparing a composite material, wherein the filler includes graphene, white carbon black, carbon black, montmorillonite carbon nanotubes and other fillers. Chinese patent CN 107857901A discloses a metakaolin rubber filler and a preparation method thereof, wherein the metakaolin rubber filler includes metakaolin, carboxylated graphene oxide, low-alkalinity sulphoaluminate cement, and fly ash. Chinese patent CN 105778156A discloses a preparation method of a novel rubber composite filler based on mercaptoene chemical reaction, wherein two commonly used fillers are subjected to ultrasonic treatment in a solvent, and then the fillers are modified by a silane coupling agent containing double bonds and mercapto groups through a photo-initiated reaction so that the two fillers are chemically bonded. Chinese patent CN106432991A discloses a preparation method of a fluororubber / nanofiller composite material, wherein the nanofiller in the method includes one or more of montmorillonite, graphene, graphene oxide, boron nitride, and halloysite.

[0004] However, there is still much room for improvement in the mechanical properties and strain-induced crystallization performance of natural rubber composites prepared by existing methods. Therefore, research on using other types of fillers to further improve the performance of composite materials is still widely concerned by researchers in this field. Summary of the invention

[0005] In current research, there are few studies on the use of MXene as a reinforcing material for natural rubber. The two-dimensional transition metal carbon / nitrogen compound (MXene), discovered in 2011, has attracted widespread attention due to its unique two-dimensional layered structure and excellent electrochemical properties. MXene has excellent photoelectric properties, flexibility, ductility and stability, and has broad prospects in the fields of electromagnetic shielding interference, supercapacitors, metal ion batteries, sensors, photocatalysis and photothermal therapy.

[0006] In order to further improve the comprehensive performance of rubber composite materials and further enrich the research on MXene as a natural rubber reinforcement material, the present invention prepares a rubber composition and a composite material using MXene / CNC combined filler as a natural rubber reinforcement material. The prepared composite material has good vulcanization processing characteristics and mechanical properties, and also has a high relative crystallinity, which improves the self-reinforcement performance of natural rubber.

[0007] This is achieved specifically through the following technical solutions:

[0008] The rubber composition comprises natural rubber and filler, wherein the filler comprises a two-dimensional transition metal carbon / nitrogen compound (MXene) and cellulose nanocrystals (CNC), and the mass ratio of the natural rubber to the filler is 100:1-8;

[0009] The MXene is selected from Ti3C2T x 、Ti3N2T x 、Ti2CT x 、Ti3CNT x 、V3C2T x 、MoC2T x or Nb3C2T x wherein T is one of -OH, -F or =O, and x is an integer of 0-3;

[0010] Preferably, the x is selected from 1, 2 or 3;

[0011] The mass of the MXene accounts for 5-75% of the mass of the filler, the mass of the cellulose nanocrystals (CNC) accounts for 2-25% of the mass of the filler, and the mass ratio of MXene to CNC is in the range of 5:1-3;

[0012] Preferably, the mass ratio of MXene to CNC is 2:1.

[0013] The CNC has a length of 100-180 nm and a diameter of 5-40 nm;

[0014] Preferably, the length of the CNC is 110-150 nm and the diameter is 10-30 nm;

[0015] The aspect ratio of the CNC is 4-15:1.

[0016] The rubber composite material comprises the rubber composition as a raw material, and further comprises a vulcanizing agent, an accelerator and an activator.

[0017] The vulcanizing agent is selected from at least one of sulfur, benzyltriphenylphosphonium chloride and a peroxide vulcanizing agent, and the peroxide vulcanizing agent is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide isopropylbenzene, tert-butyl perbenzoate or benzoyl peroxide. The mass of the vulcanizing agent is 2-4% of the mass of the natural rubber.

[0018] The accelerator is selected from at least one of 2-mercaptobenzothiazole, N-tert-butyl-2-benzothiazolesulfenamide (TBBS), diphenylguanidine and zinc dimethyldithiocarbamate, and the mass of the accelerator is 0.5%-1% of the mass of the natural rubber.

[0019] Preferably, the activator is selected from at least one of zinc oxide and stearic acid, and the mass of the activator is 0.5%-7% of the mass of the natural rubber.

[0020] In some embodiments of the present application, the composite material comprises the following raw materials in parts by weight:

[0021] 100 parts of natural rubber, 2-6 parts of MXene, 1-3 parts of CNC, 3-7 parts of activator, 0.5-1 parts of accelerator, and 2-5 parts of vulcanizer.

[0022] Preferably, the composite material comprises the following raw materials in parts by mass: 100 parts of natural rubber, 3-5 parts of MXene, 1-2 parts of CNC, 1-9 parts of activator, 0.7-0.9 parts of accelerator, and 3-4 parts of vulcanizer.

[0023] The present application also provides a method for preparing the rubber composition and the rubber composite material, comprising the following steps:

[0024] S1: Using the LiF / HCl system with relatively mild etching conditions and the centrifugation method to prepare a layered MXene suspension, and then freeze-drying it using a freeze dryer to obtain MXene nanosheet powder;

[0025] S2: Using microcrystalline cellulose as raw material, cellulose nanocrystal (CNC) dispersion was prepared by acid hydrolysis method using microcrystalline cellulose (MCC) treated with acid;

[0026] The acid used in the acid treatment can be selected from hydrochloric acid, phosphoric acid, and concentrated sulfuric acid;

[0027] Preferably, 60wt.% concentrated sulfuric acid is used to prepare the cellulose nanocrystal dispersion in the technical solution of the present application. Each acid treatment imparts specific functional groups on the surface of the nanoparticles and affects the colloidal stability. The cellulose nanocrystals produced with sulfuric acid have negatively charged sulfate groups on their surface, causing electrostatic repulsion to produce a highly stable colloidal dispersion.

[0028] The obtained rod-shaped CNC has a length of about 130nm±20nm and a diameter of about 20nm±10nm;

[0029] S3: adding MXene nanosheet powder to cellulose nanocrystal (CNC) dispersion according to the formula, ultrasonically homogenizing, adding to natural rubber, and blending with mechanical stirring, wherein the natural rubber may be natural rubber latex (NRL);

[0030] S4: adding calcium chloride solution to obtain a MXene / CNC / NR solid rubber composition, washing and drying;

[0031] S5: adding an activator, an accelerator, and a vulcanizing agent to the solid rubber composition in sequence and mixing them to obtain a mixed rubber;

[0032] S6: vulcanizing the rubber mixture to obtain a rubber composite material, wherein the vulcanization temperature is 145° C., the vulcanization pressure is 15 MPa, and the vulcanization time is slightly adjusted according to the vulcanization curve test result.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] As for the relative crystallinity performance, the strain-induced crystallization of natural rubber is the main reason for its excellent self-reinforcement performance. The addition of MXene and CNC both improves the mechanical properties and crystallization properties of rubber composites. Moreover, CNC is inserted between MXene nanosheets in the preparation of the rubber composition, which can increase the spacing between MXene sheets, thereby effectively reducing the stacking of MXene nanosheets. The two form a synergistic reinforcement effect in the rubber, and the effect of improving the mechanical properties and crystallization properties of rubber materials is greater than the improvement effect of adding MXene and CNC to the rubber material separately. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The figure is a dumbbell-shaped bar graph of relative crystallinity test cut from the rubber composite material prepared by the present invention.

[0036] Figure 2 This is the 2D-WAXD diagram of the relative crystallinity test specimen of Example 2 when stretched 500%.

[0037] Figure 3 1D-WAXD diagrams corresponding to Example 2 at tensile strains of 100%, 200%, 300%, 400% and 500% respectively. DETAILED DESCRIPTION

[0038] The filler Mxene nanosheet powder and cellulose nanocrystals (CNC) used in all examples were self-prepared, and the specific preparation method is as follows:

[0039] Layered Ti3C2T was prepared by using LiF / HCl system with relatively mild etching conditions and centrifugation method. x The suspension is freeze-dried using a freeze dryer to obtain MXene nanosheet powder;

[0040] Cellulose nanocrystal (CNC) dispersion was prepared by acid hydrolysis using microcrystalline cellulose as raw material;

[0041] Example 1

[0042] Natural rubber composite material with high self-reinforcement, composition (by mass): natural rubber 100 parts, Ti3C2T x 3 parts, cellulose nanocrystals 1 part, zinc oxide 6 parts, stearic acid 0.5 parts, accelerator TBBS 0.7 parts, sulfur 3.5 parts.

[0043] Preparation method: According to the formula, MXene nanosheet powder is added to cellulose nanocrystal (CNC) dispersion liquid and ultrasonically homogenized to obtain MXene / CNC mixed dispersion liquid. The MXene / CNC mixed dispersion liquid is added to natural rubber latex, and the mixture is mechanically stirred to obtain a MXene / CNC / NRL mixed liquid. The prepared calcium chloride solution is slowly added to the above mixed liquid, flocculated into a block solid, and a MXene / CNC / NR solid rubber composition is obtained, which is washed and dried.

[0044] On an open mill, an activator, an accelerator and a vulcanizing agent are sequentially added to a solid rubber composition, mixed and rolled evenly to obtain a mixed rubber.

[0045] The mixed rubber was further vulcanized on a flat vulcanizer to obtain a MXene / CNC / NR natural rubber composite material.

[0046] Example 2

[0047] Natural rubber composite material with high self-reinforcement, composition (by mass): natural rubber 100 parts, Ti3C2T x3 parts, cellulose nanocrystals 1.5 parts, zinc oxide 6 parts, stearic acid 0.5 parts, accelerator TBBS 0.7 parts, sulfur 3.5 parts.

[0048] The preparation is the same as Example 1.

[0049] Example 3

[0050] Natural rubber composite material with high self-reinforcement, composition (by mass): natural rubber 100 parts, Ti3C2T x 3 parts, cellulose nanocrystals 2 parts, zinc oxide 6 parts, stearic acid 0.5 parts, accelerator TBBS 0.7 parts, sulfur 3.5 parts.

[0051] The preparation is the same as Example 1.

[0052] Example 4

[0053] Natural rubber composite material with high self-reinforcement, composition (by mass): natural rubber 100 parts, V3C2T x 6 parts, cellulose nanocrystals 3 parts, zinc oxide 7 parts, accelerator 2-thiolbenzothiazole 1 part, benzyltriphenylphosphonium chloride 2 parts.

[0054] The preparation is the same as Example 1.

[0055] Example 5

[0056] Natural rubber composite material with high self-reinforcement, composition (by mass): natural rubber 100 parts, MoC2T x 3 parts, 1 part of cellulose nanocrystals, 3 parts of stearic acid, 0.7 parts of accelerator zinc dimethyldithiocarbamate, and 5 parts of dicumyl peroxide.

[0057] The preparation is the same as Example 1.

[0058] Example 6

[0059] A natural rubber composite material with high self-reinforcement, composition (by mass): 100 parts of natural rubber, Nb3C2T x 4 parts, cellulose nanocrystals 2 parts, zinc oxide 3 parts, accelerator TBBS 0.9 parts, di-tert-butyl peroxide isopropylbenzene 3.5 parts.

[0060] The preparation is the same as Example 1.

[0061] Example 7

[0062] Natural rubber composite material with high self-reinforcement, composition (by mass): natural rubber 100 parts, Ti3N2T x5 parts, cellulose nanocrystals 1 part, zinc oxide 1.5 parts, stearic acid 1.5 parts, accelerator N-tert-butyl-2-benzothiazole sulfonamide 0.8 parts, tert-butyl peroxybenzoate 2 parts.

[0063] The preparation is the same as Example 1.

[0064] Example 8

[0065] Natural rubber composite material with high self-reinforcement, composition (by mass): natural rubber 100 parts, Ti2CT x 2 parts, cellulose nanocrystals 3 parts, zinc oxide 2 parts, stearic acid 3 parts, accelerator diphenyl guanidine 0.7 parts, benzoyl peroxide 3 parts.

[0066] The preparation is the same as Example 1.

[0067] Example 9

[0068] Natural rubber composite material with high self-reinforcement, composition (by mass): natural rubber 100 parts, Ti3CNT x 6 parts, cellulose nanocrystals 2.5 parts, stearic acid 5 parts, accelerator zinc dimethyl dithiocarbamate 1 part, sulfur 2.5 parts.

[0069] The preparation is the same as Example 1.

[0070] Comparative Example 1

[0071] Natural rubber composite material, composition (by mass): natural rubber 100 parts, Ti3C2T x 0 parts, cellulose nanocrystals 0 parts, zinc oxide 6 parts, stearic acid 0.5 parts, accelerator TBBS 0.7 parts, sulfur 3.5 parts.

[0072] Preparation method: On an open mill, add an activator, a accelerator and a vulcanizer to the raw natural rubber in sequence according to a formula, mix and roll evenly to obtain a mixed rubber.

[0073] The mixed rubber is further vulcanized on a flat vulcanizer to obtain a natural rubber vulcanizate.

[0074] Comparative Example 2

[0075] Natural rubber composite material, composition (by mass): natural rubber 100 parts, Ti3C2T x 0 parts, cellulose nanocrystals 1 part, zinc oxide 6 parts, stearic acid 0.5 parts, promoter N-tert-butyl-2-benzothiazole sulfonamide (TBBS) 0.7 parts, sulfur 3.5 parts.

[0076] Preparation method: Add cellulose nanocrystals to natural rubber latex according to the formula, blend and stir mechanically to obtain a CNC / NRL mixed solution, slowly add the prepared calcium chloride solution to the mixed solution, flocculate into block-like solids, obtain a CNC / NR solid rubber composition, and wash and dry.

[0077] On an open mill, an activator, an accelerator and a vulcanizing agent are sequentially added to a solid rubber composition, mixed and rolled evenly to obtain a mixed rubber.

[0078] The mixed rubber is further vulcanized on a flat vulcanizer to obtain a CNC / NR natural rubber composite material.

[0079] Comparative Example 3

[0080] Natural rubber composite material, composition (by mass): natural rubber 100 parts, Ti3C2T x 3 parts, cellulose nanocrystals 0 parts, zinc oxide 6 parts, stearic acid 0.5 parts, accelerator TBBS 0.7 parts, sulfur 3.5 parts.

[0081] Preparation method: Add MXene nanosheet powder to natural rubber latex according to the formula, blend and stir mechanically to obtain a MXene / NRL mixed solution, slowly add the prepared calcium chloride solution to the mixed solution, flocculate into block-like solids, obtain a MXene / NR solid rubber composition, and wash and dry.

[0082] On an open mill, an activator, an accelerator and a vulcanizing agent are sequentially added to a solid rubber composition, mixed and rolled evenly to obtain a mixed rubber.

[0083] The mixed rubber is further vulcanized on a flat vulcanizer to obtain a MXene / NR natural rubber composite material.

[0084] Comparative Example 4

[0085] Natural rubber composite material, composition (by mass): natural rubber 100 parts, Ti3C2T x 5 parts, cellulose nanocrystals 0 parts, zinc oxide 6 parts, stearic acid 0.5 parts, accelerator TBBS 0.7 parts, sulfur 3.5 parts.

[0086] The preparation was the same as that of Comparative Example 3.

[0087] Experimental Example 1

[0088] Vulcanization processing characteristics test:

[0089] The obtained solid rubber composition was mixed on an open mill and rolled evenly to prepare a mixed rubber, which was then left for 24 hours to test the vulcanization processing characteristics.

[0090] The test was carried out using the RPA2000 vulcanization process analyzer at 145°C × 40min experimental conditions in accordance with GB / T9869-2014 “Disc Oscillating Rulcanizer Method for Determination of Vulcanization Characteristics of Rubber Compounds”.

[0091] Table 1 shows the vulcanization processing characteristics of Comparative Examples 1-4 and Examples 1-3. It can be seen from Table 1 that the minimum torque M of the MXene / CNC / NR natural rubber compound prepared by the present invention is L As the amount of MXene nanosheet powder added increases, as the amount of CNC added increases, the difference between the maximum torque and the minimum torque MH-ML is similar, which indicates that the degree of cross-linking is similar, and the scorch time T 10 , positive vulcanization time T 90 Quite quickly.

[0092] Table 1 Processing characteristics of MXene / CNC / NR solid rubber compositions

[0093] <![CDATA[M L / dNm]]> <![CDATA[M H / dNm]]> <![CDATA[T 10 / min]]> <![CDATA[T 90 / min]]> Comparative Example 1 0.56 9.04 2.34 8.27 Comparative Example 2 0.68 9.54 2.51 8.38 Comparative Example 3 0.81 9.22 2.87 8.71 Comparative Example 4 0.97 9.46 2.23 8.91 Example 1 1.06 9.81 2.78 8.84 Example 2 1.09 8.97 2.49 8.05 Example 3 1.14 9.33 2.57 8.47

[0094] Experimental Example 2

[0095] Mechanical properties test:

[0096] The rubber sample was vulcanized and cut into dumbbell-shaped strips with a length and width of 30×10 mm and a middle length of 6 mm. Figure 1 As shown, to be tested.

[0097] The Shore A hardness is tested using a Shore durometer in accordance with GB / T 531.1-2008 “Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore durometer method (Shore hardness)”; the tensile strength and elongation at break are tested in accordance with GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”; three specimens are made in parallel for each group.

[0098] Experimental Example 3

[0099] Relative crystallinity performance test characterization:

[0100] The rubber sample was vulcanized and cut into dumbbell-shaped strips with a length and width of 30×10 mm and a middle length of 6 mm. Figure 1 As shown, to be tested.

[0101] The D8 X-ray diffractometer from Bruker Company of Germany was used to conduct the test under the conditions of ambient temperature of 25°C and relative humidity of 60% to obtain the 2D-WAXD diagram. Figure 2 This is the 2D-WAXD image of three parallel samples when the relative crystallinity test strip of Example 2 was stretched 500%. The multiple protrusions in the crystal region visible to the naked eye are specific diffraction spots, and each diffraction spot represents a specific crystal plane.

[0102] The 2D-WAXD graph was integrated into the 1D-WAXD graph in the range of 0- to 360A by using Bruker's GADDS software. The 1D-WAXD graphs corresponding to Example 2 at 100%, 200%, 300%, 400%, and 500% tensile strains are shown in Figure 2. Figure 3 As shown, there is no obvious crystallization at 100% and 200%, the relative crystallinity is 3.8% at 300%, 10.5% at 400%, and 28.9% at 500%. Then, the Jade software is used to perform peak fitting data processing, and then the area proportions of the crystalline peak and amorphous peak are calculated, and the corresponding crystallinity is obtained.

[0103] Table 2 shows the mechanical properties of Comparative Examples 1-4 and Examples 1-3 obtained by testing Experimental Examples 2 and 3 and the relative crystallinity of the materials under 500% tensile strain. For mechanical properties, the test results show that the hardness of the MXene / CNC / NR natural rubber composite material prepared by the present invention increases with the increase of the amount of MXene and CNC added. For Comparative Examples 1, 2, and 3, as the MXene content increases, the tensile strength and elongation at break of the MXene / NR natural rubber composite material both show an increasing trend, but when the amount of MXene reaches 5 parts (Comparative Example 4), the elongation at break decreases slightly, which reflects the good reinforcement effect of MXene on the one hand. Due to the layered sheet structure of the prepared MXene, the filler is connected to the physical cross-linking point of the rubber molecular chain, and MXene is firmly embedded in the rubber matrix as a filler, so the mechanical properties of natural rubber are greatly improved. However, as the amount of MXene added continues to increase, the mechanical properties of the composite material show a downward trend. This is because a small amount of MXene agglomerates, resulting in a decrease in mechanical properties, but the overall mechanical properties of the material are still good. Therefore, the optimal amount of MXene added is 3 parts. For Comparative Example 3 and Examples 1, 2 and 3, the amount of MXene added is 3 parts. As the amount of CNC added increases, the tensile strength and elongation at break of the MXene / CNC / NR natural rubber composite material show a trend of first increasing and then decreasing. When the amount of CNC added is 1.5 parts, that is, the ratio of MXene to CNC is 2:1, the mechanical properties of the composite material are optimal. As the amount of CNC continues to increase, the tensile strength and elongation at break decrease instead. This shows that on the basis of a suitable amount of MXene added, the addition of CNC can further improve the mechanical properties of the natural rubber composite material. The optimal ratio of MXene to CNC is 2:1. Continuing to increase the amount of CNC added on the basis of this ratio will cause the mechanical properties to begin to decrease. In addition, the introduction of CNC in the above steps can produce hydrogen bond interactions with the hydrophilic groups such as -OH and -HSO3 on the MXene nanosheets through the hydrophilic groups thereon, such as -OH, thereby increasing the MXene interlayer spacing and reducing the stacking of MXene nanosheets. While reinforcing by itself as a filler, it can also improve the reinforcing effect of MXene.

[0104] Table 2 Mechanical properties and relative crystallinity of MXene / CNC / NR natural rubber composites

[0105] Shore A Hardness Tensile strength / MPa Elongation at break / % Relative crystallinity / % Comparative Example 1 40 14.7 483.6 9.4 Comparative Example 2 42 16.5 495.1 13.5 Comparative Example 3 44 20.4 500.4 18.4 Comparative Example 4 46 19.5 489.5 17.5 Example 1 45 24.2 503.4 25.6 Example 2 46 25.7 523.1 28.9 Example 3 48 23.9 486.8 24.8

[0106] For the relative crystallinity performance, the strain-induced crystallization of natural rubber is the main reason for its excellent self-reinforcement performance, which is of great significance for studying the material response of natural rubber under strain and evaluating its performance. The wide-angle X-ray diffraction WXRD technology is used to distinguish the contribution of different crystalline and amorphous regions of the sample to the scattering intensity, which can provide the crystallinity information of the natural rubber sample. Here, we stretched the natural rubber composite material by 500% and measured it by WXRD method and fitted it. As shown in Table 2, with the increase of MXene content, the relative crystallinity of the natural rubber composite material first increased and then decreased. This is because after adding an appropriate amount of MXene nanosheets, they are dispersed in the NR matrix in a peeled layered state. These sheets are preferentially oriented during the deformation process of the natural rubber composite material, and drive the NR orientation, sensitively inducing crystallization, but continuing to increase the amount of MXene addition will cause MXene stacking and lead to performance degradation. As the CNC content increases, the relative crystallinity of the natural rubber composite material increases first and then decreases. This is because the CNC prepared by the present invention has a relatively high aspect ratio and a high specific surface area, which can significantly improve the crystallization index. At the same time, CNC is inserted between MXene nanosheets in the preparation of the rubber composition, which can increase the spacing between MXene sheets, thereby effectively reducing the stacking of MXene nanosheets. Therefore, MXene and CNC can form a synergistic reinforcement effect in the composite material system. The improvement of the mechanical properties and relative crystallinity of the rubber composite material by adding MXene and CNC separately in Comparative Examples 2 and 3 is less than the improvement of the mechanical properties and relative crystallinity of the rubber composite material by adding MXene and CNC simultaneously in Example 1, which also proves that MXene and CNC have a synergistic reinforcement effect. However, excessive increase will also reduce the mechanical properties and relative crystallinity.

Claims

1. A rubber composition, characterized in that: Includes natural rubber and fillers; Wherein, the filler includes two-dimensional transition metal carbon / nitrogen compound MXene and cellulose nanocrystal CNC.

2. The rubber composition according to claim 1, characterized in that The mass ratio of the natural rubber to the filler is 100:1-8.

3. The rubber composition according to claim 1, characterized in that The MXene is selected from Ti3C2T x 、Ti3N2T x 、Ti2CT x 、Ti3CNT x 、V3C2T x 、MoC2T x or Nb3C2T x wherein T is one of -OH, -F or =O, and x is an integer of 0-3.

4. The rubber composition according to claim 1, characterized in that The mass ratio of the MXene to CNC ranges from 5:1 to 3.

5. The rubber composition according to claim 1, characterized in that The length of the CNC is 100-180 nm, and the aspect ratio is 4-15:

1.

6. A rubber composite material, characterized in that: A rubber composition comprising any one of claims 1 to 5.

7. The rubber composite material according to claim 6, characterized in that: Also contains activators, accelerators and vulcanizing agents.

8. The rubber composite material according to claim 6 or 7, characterized in that: The composition comprises the following components in parts by mass: 100 parts of natural rubber, 2-6 parts of MXene, 1-3 parts of CNC, 3-7 parts of activator, 0.5-1 parts of accelerator and 2-5 parts of vulcanizer.

9. The rubber composite material according to claim 8, characterized in that: The composition comprises the following components in parts by mass: 100 parts of natural rubber, 3-5 parts of MXene, 1-2 parts of CNC, 1-9 parts of activator, 0.7-0.9 parts of accelerator, and 3-4 parts of vulcanizer.

10. The rubber composite material according to claim 7, characterized in that: The vulcanizing agent is selected from at least one of sulfur, benzyltriphenylphosphonium chloride or a peroxide vulcanizing agent, and the peroxide vulcanizing agent is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide isopropylbenzene, tert-butyl perbenzoate or benzoyl peroxide.

11. The rubber composite material according to claim 7, characterized in that: The accelerator is selected from at least one of 2-mercaptobenzothiazole, N-tert-butyl-2-benzothiazolesulfenamide, diphenylguanidine or zinc dimethyldithiocarbamate.

12. The rubber composite material according to claim 7, characterized in that: The activator is selected from at least one of zinc oxide and stearic acid.

13. A method for preparing the rubber composite material according to any one of claims 6 to 12, characterized in that: The following steps are involved: S1: treating microcrystalline cellulose with acid to obtain a cellulose nanocrystal dispersion; S2: adding MXene nanosheets into cellulose nanocrystal dispersion to obtain MXene / CNC mixed dispersion; S3: adding the MXene / CNC mixed dispersion into natural rubber to obtain a MXene / CNC / NR mixed dispersion; S4: adding a calcium chloride solution to the MXene / CNC / NR mixed solution to obtain a MXene / CNC / NR solid rubber composition; S5: adding an activator, an accelerator and a vulcanizing agent to the MXene / CNC / NR solid rubber composition and mixing the mixture to obtain a mixed rubber; S6: vulcanizing the rubber mixture to obtain a rubber composite material.

Citation Information

Patent Citations

  • Oxidized grapheme / carbon black rubber nanocomposite and preparation method thereof

    CN103224656A

  • Novel rubber compound stuffing preparing method based on mercapto-alkene chemical reaction

    CN105778156A

  • Preparing method of fluororubber / nanofiller composite material

    CN106432991A

  • Metakaolin rubber filler and preparation method thereof

    CN107857901A

  • Natural rubber composite material and preparation method thereof

    CN108299687A

Cited By

  • High-strength butyl regenerated rubber for automobile inner tube and preparation method of high-strength butyl regenerated rubber

    CN120554766A

  • Rubber nano composite material containing modified MXene and preparation method thereof

    CN122145895A